Analytical review of approaches to providing safety when substantiating hygienic standards for chemicals contents in ambient air - P.Z. Shur; A.A. Khasanova (Analiz Riska Zdorovʹû, 2021)
A necessity to harmonize Russian sanitary-epidemiologic approaches with international standards is fixed in the federal legislation in the RF; given that, it seems vital to harmonize standards for ambient air quality taking into account a period of their averaging. To do that, previously methodical approaches were suggested to substantiating average annual MPC of chemicals in ambient air as per health risk criteria. The research goal here was to make a review of previously applied and newly created methodical approaches to establishing average annual MPC taking into account an extent to which they were harmonized with international approaches and their capacity to provide safety for population. As per results obtained via the performed literature review, we spotted out key elements in methodical approaches applied in the RF and abroad when substantiating standards for ambient air quality taking into account chronic inhalation exposure; the further analysis was performed in accordance with them. It was detected that approaches applied to establish average annual MPC were partially harmonized since they didn’t involve using threshold levels (BMC, BMCL); use of results obtained in previous studies to establish starting points in developing hygienic standards does not allow taking all the existing uncertainties into account. It seems impossible to estimate their safety as per health risk criteria due to absence of relevant parameters. Methodical approaches to substantiating average annual MPC as per health risk criteria are fully harmonized. Thus, they involve using BMC and BMCL for determining starting points when standards are being developed; values for such starting points can be established, among other things, as per data obtained via analyzing results of previous studies and are also supplemented when it comes down to taking uncertainty factors into account. Safety of developed average annual MPC is provided, among other things, due to obtained standards being verified as per acceptable (permissible) risk criteria. Given that, they can be used for developing harmonized average annual MPC.